2015
DOI: 10.1038/bmt.2015.177
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model predicting autologous transplantation outcomes in children, adolescents and young adults with Hodgkin lymphoma

Abstract: Autologous hematopoietic cell transplantation (AutoHCT) is a potentially curative treatment modality for relapsed/refractory Hodgkin lymphoma (HL). However, no large studies have evaluated pre-transplant factors predictive of outcomes of AutoHCT in children, adolescents and young adults (CAYA, age <30 years). In a retrospective study, we analyzed 606 CAYA patients (median age 23 years) with relapsed/refractory HL who underwent AutoHCT between 1995–2010. The probabilities of progression free survival (PFS) at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
6

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 40 publications
2
35
1
6
Order By: Relevance
“…High‐dose chemotherapy followed by autologous hematopoietic cell transplantation (auto‐HCT) remains the standard treatment for medically fit patients with relapsed or refractory aggressive lymphomas . Reported survival rates 3 to 5 years after auto‐HCT for classic Hodgkin lymphoma (cHL) and diffuse large B‐cell lymphoma (DLBCL) range from 40% to 70% . Treatment failure is most commonly due to relapse or progression of the underlying disease, which primarily occurs within the first 2 years after auto‐HCT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐dose chemotherapy followed by autologous hematopoietic cell transplantation (auto‐HCT) remains the standard treatment for medically fit patients with relapsed or refractory aggressive lymphomas . Reported survival rates 3 to 5 years after auto‐HCT for classic Hodgkin lymphoma (cHL) and diffuse large B‐cell lymphoma (DLBCL) range from 40% to 70% . Treatment failure is most commonly due to relapse or progression of the underlying disease, which primarily occurs within the first 2 years after auto‐HCT .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Reported survival rates 3 to 5 years after auto-HCT for classic Hodgkin lymphoma (cHL) and diffuse large B-cell lymphoma (DLBCL) range from 40% to 70%. [2][3][4][5][6][7][8] Treatment failure is most commonly due to relapse or progression of the underlying disease, which primarily occurs within the first 2 years after auto-HCT. 1 For those patients who survive the initial post-auto-HCT period, long-term outcomes are not well described.…”
Section: Introductionmentioning
confidence: 99%
“…With the observation that complete response by PET/CT is associated with higher survival following AHSCT, 16 evaluation of novel combinations to improve CR rates would be of value, perhaps in conjunction with adult cooperative groups as part of an AYA initiative. Given that the median age at relapse is in mid adolescence, consideration for lowering the age for eligibility for trials would greatly improve access to novel agents for adolescents with HL.…”
Section: Priorities For Clinical Researchmentioning
confidence: 99%
“…A recent CIBMTR analysis of 671 patients ,30 years who underwent AHSCT for relapsed/ refractory HL reported progression free survival and overall survival rates of 56% and 73%, respectively. 16 Clinical risk factors including first remission ,12 months, poor performance status, chemoresistance, extranodal disease at relapse, and receipt of regimens other than ABVD/ABVD-like for first line therapy predict reduced survival post AHSCT. In contrast, patients with late relapse of low-stage disease are predicted to have excellent outcomes with conventional chemotherapy or chemoradiotherapy, and thus may be able to avoid the acute and long-term toxicity associated with AHSCT.…”
Section: Lessons From Recent Clinical Trials In Children and Adolescementioning
confidence: 99%
“…Multiple factors have been identified that correlate with outcome to salvage therapy, including advanced stage, extranodal disease, B symptoms, time to relapse, and extent of prior therapy . The high ORR in our cohort may be a reflection of patient characteristics: all of our patients were at first relapse or progression, only one had prior radiotherapy, and none had B symptoms.…”
Section: Discussionmentioning
confidence: 84%